Pembaharuan Pengaturan Hukum Pidana Justice Collaborator Dalam Hukum Positif Indonesia - Permatasari, Mutiara; A, Syaifullah Yophi; Andrikasmi, Sukamarriko (Peneliti.net, 2024)
The law always moves dynamically following changes and developments over time in the concept of criminal law reform. The large number of organized criminal acts ultimately gave rise to the idea of perpetrators working together (Justice Collaborator). The legal basis governing Justice Collaborators is contained in Law Number 31 of 2014 concerning Protection of Witnesses and Victims; and Supreme Court Circular Letter (SEMA) No. 4 of 2011 concerning Treatment of Criminal Whistleblowers and Justice Collaborators. In Certain Criminal Cases. In cases where the defendant wants to apply for status as a Justice Collaborator, even defendants who have already obtained status as a Justice Collaborator receive unfair treatment due to the legal vacuum of this legal basis. This legal vacuum makes the author want to research how indicators a person can be categorized as a Justice Collaborator in accordance with Indonesian positive law, what is the ideal concept of Justice Collaborator arrangements for perpetrators of criminal acts in Indonesia. The aim of this research is to explain the indicators that a person can be categorized as a Justice Collaborator and to formulate an ideal concept for regulating Justice Collaborators for perpetrators of criminal acts in Indonesia. This type of research is normative juridical, that is, legal research is carried out by examining library materials. The results of this research are the Justice Collaborator indicators in SEMA Number 4 of 2011, namely being aware of their mistakes and admitting to criminal acts, not being the main perpetrator, being cooperative and providing clear information, uncovering criminal acts effectively or uncovering other perpetrators, and the Public Prosecutor The lawsuit states the role that the perpetrator has been assigned. As the legal basis regarding Justice Collaborator still has deficiencies based on cases in Indonesia, the researcher provides an ideal concept, namely that there are deficiencies in the regulations regarding